Answer:
-11x+12
Step-by-step explanation:
(x^2-4x+3)-(x^2+7x-9)
x^2-x^2-4x-7x+3-(-9)
-11x+3+9
-11x+12
Answer:
they can??!!!
Step-by-step explanation:
omigod wowoow
Answer:
rational
Step-by-step explanation:
Answer:
![\boxed{D = 69}](https://tex.z-dn.net/?f=%5Cboxed%7BD%20%3D%2069%7D)
Step-by-step explanation:
The given quadratic equation is:
![3x^2-9x+1 = 0](https://tex.z-dn.net/?f=3x%5E2-9x%2B1%20%3D%200)
Comparing it with the standard form of Quadratic Equation
, we get:
a = 3, b = -9 and c = 1
Discriminant = b² - 4ac
D = (-9)²-4(3)(1)
D = 81 - 12
D = 69